The Digital Frontier: How Indonesia's Politics is Shaping the Fight against Human Trafficking - Molasy, Honest Dody (Universitas Terbuka, 2024)
This article examines the complex intersection between Indonesia’s political landscape and its efforts to combat human trafficking, focusing on integrating digital technologies. Human trafficking remains a critical and persistent issue in Indonesia, exacerbated by systemic challenges such as corruption, weak law enforcement, and socio-economic vulnerabilities. Adopting a qualitative research approach, this study combines policy analysis and case studies to evaluate the effectiveness of current anti-trafficking strategies. Findings reveal that digital tools, including artificial intelligence, big data analytics, and blockchain technology, hold significant potential for enhancing victim identification, streamlining case management, and improving inter-agency coordination. Public-private partnerships emerge as vital in driving technological innovation and fostering community engagement. However, the study also identifies major obstacles, including unequal digital infrastructure between urban and rural areas, cybersecurity risks, and the limited digital capacity of law enforcement agencies. Given the urgency of addressing human trafficking as a national and regional concern, the article advocates for Indonesia to take a leadership role in Southeast Asia by advancing comprehensive, tech-driven strategies that align with international human rights frameworks. This approach strengthens Indonesia’s anti-trafficking architecture and provides a scalable model for other nations confronting similar challenges. By illuminating the interplay between politics, technology, and human rights, this research contributes to the evolving discourse on trafficking prevention. It offers actionable insights for policymakers, civil society, and international stakeholders working to combat this global crime.